Verification of the Role of ADAMTS13 in the Cardiovascular Disease Using Two-Sample Mendelian Randomization - Ye, Zixiang; Zheng, Jingang (Frontiers in Genetics, 2021)
Objective: ADAMTS13 plays a crucial role in several diseases. Many observational studies have reported the relationship between ADAMTS13 and some cardiovascular diseases, but have drawn different conclusions that are likely attributed to confounding factors lacking adjustment. Identifying the role of ADAMTS13 in cardiovascular diseases is pivotal for prevention as well as early intervention in patients with latent cardiovascular disease. This study aims to estimate whether the level and activity of ADAMTS13 are causally associated with common cardiovascular diseases. Methods: We applied a two-sample Mendelian randomization approach incorporating genome-wide association summary statistics to verify the causal association between ADAMTS13 level, as well as activity, and cardiovascular diseases. Results: Lower ADAMTS13 activity was causally associated with the increased risks for coronary heart diseases (b=–0.0041, se=0.0019, p<0.05) as well as myocardial infarction (b=–0.0048, se=0.0022, p<0.05). Standard inverse-variance weighted Mendelian randomization results suggested no genetic support for a causal association between ADAMTS13 level and cardiovascular diseases including coronary heart disease, myocardial infarction, atrial fibrillation, heart failure, and venous thromboembolism (p>0.05). Conclusion: The causal effect of lower ADAMTS13 activity on the increased odds of having cardiovascular diseases was coronary heart disease, myocardial infarction.